Comparative characteristics of the cellular immune response to SARS-CoV-2 during infection and post-vaccination - S. N. Klyueva; S. A. Bugorkova; A. L. Kravtsov; T. N. Kashtanova; V. A. Kozhevnikov (Медицинская иммунология, 2024)
An important area of research concerns monitoring of immune response features in patients with SARS-CoV-2 infection as well as their analysis, as compared with characteristics of vaccine-mediated protection, in order to specify the determinants of cellular immune response. The aim of our work was to compare the state of cellular immune response in patients who underwent COVID-19, and in persons vaccinated with a peptide vaccine preparation. The study involved volunteers who suffered with COVID-19 of varying severity (n = 30), as well as persons who completed the full course of vaccination with the peptide vaccine (n = 27). For comparison, we took blood specimens from the volunteers before vaccination. Immunophenotyping of leukocytes was performed by the Lyse/No-Wash procedure (BD Bioscience, USA), and Cyto-Stat monoclonal antibodies (CD45-FITC, CD4-PE, CD8-ECD, CD3-PC5), CD45RA-PC7, CD45RO-PE (Beckman Coulter, USA), and analyzed with a DakoCytomation flow cytometer (Denmark). Determination of intracellular IFNγ (CD4+IFNγ+) was performed with the standard technique. Cytokine production was determined using reagent kits for detection of IFNγ, TNFα, IL-4, IL-8, IL-10 (Vector-Best JSC, Russia) with automatic enzyme immunoassay analyzer LAZURIT (Dynex Technologies, USA). As based on the results obtained, we have shown that cellular immunity was developed after vaccination and infection with COVID-19. However, the most pronounced immune response was recorded in the COVID-19 reconvalescents, i.e., more than 60% of these patients showed an increased number of CD4+T-memory helper cells (8.7 (0.5-12.1) % versus 0.3 (0.1-0.5) % in the comparison group, p < 0.05) as well as proportion of CD4+IFNγ+T lymphocytes (4.2 (1.8-4.3) % versus 0.4 (0-0.8) % in the comparison group, p < 0.05). Moreover, we revealed an increased functional reserve of cells in terms of TNFα, IL-8, IL-10 production. One month after vaccination of volunteers with the peptide-based preparation, the total pool of memory T lymphocytes was apparently dominated by CD8+T memory cells (CD45+CD8+CD45RA-CD45RO+). A significant increase was found in the average levels of CD4+IFNγ+ activated cells (8.2-fold), as well as in values of ConA-induced IL-4 production (3.3 (1.1-4.5) pg/mL, and 2.8 (1.7-3.9) pg/mL, respectively versus 1.3 (0.1-2.4) pg/mL in the control group, p < 0.05). The data obtained are in accordance with information available in the literature concerning development of cellular immune responses to SARS-CoV-2, which results from a past illness, or measures for the specific prevention of COVID-19. Further search for cellular correlates of protection against a new coronavirus infection will allow us to revise the current vaccination strategy and develop an optimal approach to COVID-19 prevention.